Efektivitas Pemberian Kredit Pada Lembaga Perkreditan Desa (LPD) Desa Pakraman Rangkan, Kecamatan Sukawati, Kabupaten Gianyar, Provinsi Bali - Dwitya Candra Yasa; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
Bali creates an economy that is able to prosper its people so that there are several institutions. One of which is a microfinance institution, namely Village Credit Institution (Lembaga Perkreditan Desa) located in all Pakraman villages in Bali. The purpose of establishing the Village Credit Institution (LPD) is to support rural economic development by improving people’s saving habits, providing credit for small-scale businesses. Creditors can provide credit to their members, and members who borrow (debtors) can return the credits obtained according to the agreement they made. Success can be defined as effectiveness. This research was conducted through a qualitative descriptive with empirical methods. Sources of data used in the form of primary data obtained from observations to LPD Pakraman Rangkan Village and secondary funds obtained from books and related references. These data sources were then processed qualitatively to obtain data that were relevant to the issues raised and presented in full in relation to certain aspects related to the problem and then analyzed its validity. The results showed that lending to the LPD of Pakraman Rangkan Village has not been implemented effectively because the LPD disburses credit only to people who have collateral goods, without prioritizing the people around Pakraman Rangkan Village.